2010
DOI: 10.1371/journal.pone.0010675
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Natural Killer but Not Effector CD8 T Lymphoyctes in Three Consecutive Cases of Severe/Lethal H1N1/09 Influenza A Virus Infection

Abstract: BackgroundThe cause of severe disease in some patients infected with pandemic influenza A virus is unclear.Methodology/Principal FindingsWe present the cellular immunology profile in the blood, and detailed clinical (and post-mortem) findings of three patients with rapidly progressive infection, including a pregnant patient who died. The striking finding is of reduction in natural killer (NK) cells but preservation of activated effector CD8 T lymphocytes; with viraemia in the patient who had no NK cells. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 35 publications
4
61
1
1
Order By: Relevance
“…In addition, it is possible that the changes in the levels of NK lymphocytes may reflect nonspecific effects of a systemic inflammatory process rather than a specific response to influenza virus. However, our results are in apparent contradiction with those of previous reports showing diminished levels of NK cells in patients with influenza infection (18,19). It is feasible that the times of blood sampling, the degrees of disease severity, the virus strains involved, and the genetic backgrounds of the patients studied may account, at least in part, for these contrasting results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, it is possible that the changes in the levels of NK lymphocytes may reflect nonspecific effects of a systemic inflammatory process rather than a specific response to influenza virus. However, our results are in apparent contradiction with those of previous reports showing diminished levels of NK cells in patients with influenza infection (18,19). It is feasible that the times of blood sampling, the degrees of disease severity, the virus strains involved, and the genetic backgrounds of the patients studied may account, at least in part, for these contrasting results.…”
Section: Discussioncontrasting
confidence: 99%
“…Over the past decade, several studies have addressed the role of NK cells and their receptors involved in the induction of cell killing in influenza virus infections (8,9,10,12,15,19,22,23). Because NK lymphocytes do not require prior sensitization to exert their lytic effects on infected cells, they may have a key protective role against emergent pathogens or new variants or strains of different viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients severely ill after H1N1/09 infection, reduction in NK cells, but preservation of T lymphocytes, was observed. 86 The NK cells are present in maternal decidua in large numbers where they can destroy virus-infected cells via a perforin-dependent mechanism, leading to apoptosis induction. 36 …”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…The rapid decrease of virus-specific CD8 ϩ T cells from the blood may reflect migration of these cells to the site of infection (12). It has been reported that the frequency of Tm ϩ CD8 ϩ T cell is low after 2009 H1N1 influenza virus infection (6). However, T cell responses were analyzed with Tm in two patients only and at a late time point after the onset of clinical symptoms.…”
mentioning
confidence: 99%